Qanaah Enterprise: Integrating Faith, Technology, and Sustainability in Smart Organic Farming - Yahya, Rohaziah; Sarif, Suhaimi; Zainudin, Dolhadi; Abdul Razak, Dzuljastri (IIUM Journal of Case Studies in Management, 2025)
This case study explores Qanaah Enterprise, a faith-driven agricultural business in rural Malaysia that embodies Islamic values of taqwa (God-consciousness), qanaah (contentment), halalan toyyiban food ethics, and Sejahtera sustainability. Founded by Mr. Qanaah, the enterprise began as a small MD2 pineapple farm and evolved into a values-based model of smart farming integrating artificial intelligence (AI), circular economy principles, and ethical governance. Prioritizing local food security and community well-being over export-driven growth, Qanaah Enterprise serves B40 households with nutritious, chemical-free produce while donating surplus to mosques and orphanages weekly. Through strategic partnerships with local universities and the Department of Agriculture, the enterprise adopts data-driven techniques for sustainable irrigation, pest control, and resource management. The case examines how Islamic principles shape business decisions, including the rejection of riba-based financing and unethical scaling strategies. Instead, the enterprise relies on crowdfunding, waqf, and qard hasan to finance operations, guided by sincerity (ikhlas), service (khidmah), and trust in divine provision (tawakkul). It documents stories of empowerment—such as youth reintegration, single mother entrepreneurship, and differently-abled employment—reflecting a model where farming becomes ibadah (worship) and enterprise becomes amanah (trust). The farm functions as a learning hub, spiritual platform, and community cooperative grounded in Tawhidic epistemology and ummatic excellence. This case offers practical insights for entrepreneurship, agribusiness, and faith-based management education, presenting Qanaah Enterprise as a replicable example of how small-scale enterprises can balance sustainability, technology, and spirituality—creating meaningful impact with purpose beyond profit. Keywords: Smart Agriculture, ESG, SDG, Circular Economy, Qanaah, Sejahtera Sustainability, Halalan Toyyiban, Islamic Entrepreneurship